If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4 + -7(n) = -65 Solving 4 + -7n = -65 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + -7n = -65 + -4 Combine like terms: 4 + -4 = 0 0 + -7n = -65 + -4 -7n = -65 + -4 Combine like terms: -65 + -4 = -69 -7n = -69 Divide each side by '-7'. n = 9.857142857 Simplifying n = 9.857142857
| 18x+6x+2x-3+14(3-2)=0 | | -21+k=k-2k | | 0.6-1.2x=5.4x-0.1 | | 3(m+6)=2(m-1) | | 2+3y-2y=14 | | 3(m+6)=2(m-6) | | 12*0.4+3(0.4-2)=0 | | x^2+10x+25-17=0 | | -75+16y+3=5(5y-5)-2 | | 5.5m-5.5m=-12 | | 5(x+4)=4(x+6) | | 15(3+x)= | | 17-2x=7x-11 | | 5x+4=9+3x | | 67=3(2n+7)-2 | | 4y=42-3y | | 21x+16=17x+26 | | 4x-3=4(x-5) | | -2y-18=5y+17 | | 5x-20y=30 | | -6/5(1+y)+y=-13/5 | | 9x^7/15x | | -7-5(8n-8)=193 | | 3x=3+3y | | 3x-4=7x-1-3x | | -77=-7(-5x-4) | | 20x-5=40x-3 | | 32x+4=68 | | -3(z+4)=8-2z | | 18+7c=32-3c | | -65=-5(1-4x) | | 7x-3+2x=9x-8x-17 |